Increasing Food Security and Farming System Resilience in East Africa through Wide-Scale Adoption of Climate-Smart Agricultural Practices - Winowiecki, Leigh Ann; Läderach, Peter R.D.; Mwongera, Caroline; Twyman, Jennifer; Mashisia, Kelvin; Okolo, Wendy; Eitzinger, Anton; Rodríguez Sánchez, Beatriz (2015)
The overall project goal is to improve food security and farming system resilience of smallholder mixed crop-livestock farmers in East Africa while mitigating climate change through wide-scale adoption of climate-smart agriculture (CSA). The project integrates interdisciplinary approaches, including participatory research, integrating a meta-analysis of CSA practices, real-time land and soil health assessments, crop suitability modelling, socio-economic appraisals and multi-dimensional trade-off analyses, as well as on-farm participatory evaluations of CSA to identify, test, implement, and outscale locally appropriate CSA practices